PENGARUH PENAMBAHAN TEPUNG DAUN SINGKONG (MANIHOT ESCULENTA) DENGAN LEVEL YANG BERBEDA TERHADAP KONSUMSI DAN KONVERSI PADA PAKAN PUYUH (COTURNIX-COTURNIX JAPONICA) - Baharuddin, Rahmat; Amin, Nurul; Dwi Novieta, Intan (Jurusan Peternakan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
Abstract: This study aims to find out how the effect of adding cassava leaf flour (Manihot esculenta) to quail feed on consumption and conversion as an alternative feed using a completely randomized design (CRD) method with four treatments three replicates P0 : Without Control Treatment 0%, P1 : Cassava leaf powder (Manihot esculenta) 1% in feed, P2 : Cassava leaf powder (Manihot esculenta) 3% in feed, P3 : Cassava leaf powder (Manihot esculenta) 5% in feed. The results of this study indicated that the addition of cassava leaf flour (Manihot esculenta) had no significant effect (P>0.05) on quail feed consumption and conversion. The average feed consumption was P0 (343.89 gr/head), P1 (349.32 gr/head), P2 (356.44 gr/head) and P3 (347.18 gr/head) and the average feed conversion was P0 (2.094gr), P1 ( 2.114gr), P2 (1.995gr), and P3 (2.046gr). The treatment that can be used for quail livestock applications is treatment P1 with the addition of cassava leaf flour as much as 1% Keywords : Cassava leaf flour (Manihot esculenta), alternative feed, consumption and conversion.